Creating trust through communication within a knowledge ecosystem : an empirical perspective of SMEs - Shahzad, Khuram; Hafeez, Shahid (Routledge, 2023)
The interest toward mutual trust in the ecosystem is increasing in the current literature. Therefore, the purpose of this research is to explore the significant role of effective communication in building mutual trust in knowledge-based ecosystem collaborations as small and medium enterprises (SMEs) need to collaborate across organizational boundaries due to the lack of internal resources. We employ a qualitative study and collected empirical data through a focus group workshop and semi-structured interviews with SMEs and other stakeholders in a regional ecosystem. Our findings suggest that knowledge exchange with other ecosystem actors is based on emplaced trust among the partnering actors, where open and transparent communication and information sharing are the keystone determinants of building trustworthy relationships in the ecosystem. Furthermore, we have found that close geographical proximity and intermediary facilitation activities are critical in developing efficient communication, resulting in developed mutual trust. Co-location helps in utilizing personal relations, sharing transparent and open information, and collaborating with inter-organizational teams in close proximity, while intermediaries initiate collaborations between different ecosystem actors and function as trust-bridging entities which drive SMEs to develop know-how of their partners. Relevant theoretical and managerial implications are also discussed.
Keywords: Mutual trust; knowledge ecosystem; SMEs; intermediary organizations; small and medium-sized enterprises; communication; fi=Tuotantotalous|en=Industrial Management|